PENGARUH PENGUNGKAPAN ENTERPRISE RISK MANAGEMENT DAN KUALITAS LAPORAN KEUANGAN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN PENERIMA CORPORATE IMAGE AWARD - Indhira Yuliyana Rosya; Nova Novita (Journal of Accounting, Management and Islamic Economics, 2023)
This study aims to determine the effect of enterprise risk management disclosure on the quality of financial reports in companies receiving corporate image awards. This research was conducted on companies receiving the Corporate Image Award in the categories of national airlines, car tires, two-wheeled automotive, four-wheeled automotive, coal mining, oil & gas mining, and cement for the 2015-2019 period. This study uses purposive sampling technique and secondary analysis using quantitative methods. This observation uses the random effect method and multiple linear regression analysis which is used to test the hypothesis. The results of this study indicate that the disclosure of enterprise risk management has a negative effect on the quality of financial statements, and firm size can strengthen the effect of using enterprise risk management disclosures on the quality of financial statements.